A variational approach to Navier–Stokes. (15th November 2018) - Ortiz, Michael; Schmidt, Bernd; Stefanelli, Ulisse
Abstract: We present a variational resolution of the incompressible Navier–Stokes system by means of stabilized weighted-inertia-dissipation-energy (WIDE) functionals. The minimization of these parameter-dependent functionals corresponds to an elliptic-in-time regularization of the system. By passing to the limit in the regularization parameter along subsequences of WIDE minimizers one recovers a classical Leray–Hopf weak solution.